2007
DOI: 10.1097/mpa.0b013e31812e965e
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation at the Clinical Onset of Chronic Pancreatitis and Risk of Pancreatic Calcifications

Abstract: Smoking cessation in the first years from the clinical onset of CP reduces the risk of developing pancreatic calcifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…A recent population-based study identified the attributable risk associated with smoking for pancreatitis to be 46% [18] . Clinical data also support associations between smoking and CP risk and progression [19][20][21][22][23] . Thus, the available evidence points toward a strong role for smoking in the development and progression of CP.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent population-based study identified the attributable risk associated with smoking for pancreatitis to be 46% [18] . Clinical data also support associations between smoking and CP risk and progression [19][20][21][22][23] . Thus, the available evidence points toward a strong role for smoking in the development and progression of CP.…”
Section: Discussionmentioning
confidence: 89%
“…Smoking has been linked to the evolution from acute to CP [19] and progression of CP [20][21][22]. Moreover, smoking cessation after CP diagnosis may slow disease progression [23]. Therefore, recognition of smoking as a risk factor for CP provides an opportunity for counseling and smoking cessation as an intervention for primary and secondary prevention.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, current smokers were at a 7.8-times greater risk than that of non-smokers (95% CI 2.2, 27.3) for CP; whereas ex-smokers were at decreased risk compared to current smokers (OR 1.7, 95% CI 0.4, 6.3) [5]. In another study, ex-smokers who quit smoking within 5 years of CP diagnosis were at decreased risk for pancreatic calcifications compared with never-smokers [19]. The classification of smoking as current-smoker vs. non-smoker seems more clinically applicable since clinicians do not always probe for remote smoking habits.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence and hence no recommendation for smoking cessation in CP and PEI despite some reports, 5,15 even in acute pancreatitis. [2][3][4][5] Smoking cessation is recommended (Evidence 3b, recommendation A).…”
Section: General Measurementsmentioning
confidence: 99%